1997
DOI: 10.4319/lo.1997.42.3.0529
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification and denitrification in the rhizosphere of the aquatic macrophyte Lobelia dortmanna L.

Abstract: Nitrogen and 0, transformations were studied in sediments covered by Lobelia dortmanna L.; a combination of 15N isotope pairing and microsensor (0,, NO,-, and NH,+) techniques were used. Transformation rates and microprofiles were compared with data obtained in bare sediments. The two types of sediment were incubated in doublecompartment chambers connected to a continuous flow-through system.The presence of L. dortmanna profoundly influenced both the nitrification-clenitrification activity and porewater profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The measured rates of total denitrification (D 14 ) varied between 0 and 34.5 lmol N/m 2 h in this study are in extremely good agreement with those of between 2 and 35 lmol N/m 2 h that have previously been reported in both non-vegetated tidal flats and seagrass meadows throughout the world (Risgaard-Petersen and Jensen 1997;Herbert 1999;Ottosen et al 1999;Risgaard-Petersen and Ottosen 2000;Welsh et al 2000Welsh et al , 2001. Unlike the previous work by Welsh et al (2000) who found no statistical difference in the rates of total denitrification throughout the year at the same sample site, statistically significant differences (Supporting Information Table S3; p < 0.05) were found in the rates of denitrification at the different sites in this study throughout the year.…”
Section: Denitrificationsupporting
confidence: 91%
See 1 more Smart Citation
“…The measured rates of total denitrification (D 14 ) varied between 0 and 34.5 lmol N/m 2 h in this study are in extremely good agreement with those of between 2 and 35 lmol N/m 2 h that have previously been reported in both non-vegetated tidal flats and seagrass meadows throughout the world (Risgaard-Petersen and Jensen 1997;Herbert 1999;Ottosen et al 1999;Risgaard-Petersen and Ottosen 2000;Welsh et al 2000Welsh et al , 2001. Unlike the previous work by Welsh et al (2000) who found no statistical difference in the rates of total denitrification throughout the year at the same sample site, statistically significant differences (Supporting Information Table S3; p < 0.05) were found in the rates of denitrification at the different sites in this study throughout the year.…”
Section: Denitrificationsupporting
confidence: 91%
“…Variable impacts of vegetation on denitrification rates compared to non-vegetated sediments have also been recorded in the literature. Risgaard-Petersen and Jensen (1997) found that the presence of the wetland macrophyte Lobelia dortmanna greatly stimulated the rate of denitrification under both light and dark conditions. In contrast Risgaard-Petersen and Ottosen (2000) found no significant difference in total denitrification rates between nonvegetated sediments and those containing Zostera marina.…”
Section: Denitrificationmentioning
confidence: 97%
“…DNT rates measured in ISO sediments were 8-to 100-fold higher than in bare sediments and 18-to 370-fold higher than in MIX-sediments. These increases are higher than the values measured in other lake sediments after comparing ROL vs. non vegetated sediments, i.e., within the range 0.1-11.7 increase (Bodelier et al 1996;Risgaard-Petersen and Jensen 1997;Karjalainen et al 2001). Differences appear to be higher under nutrient-limitation conditions as is the case of the ultraoligotrophic waters in the Pyrenean area.…”
Section: Discussionmentioning
confidence: 51%
“…Terrestrial and aquatic denitrification (DNT) and anammox processes are of special interest because they represent the only permanent removal pathway whereby bioavailable N is returned to inert N 2 gas (Rockstr€ om et al 2009). The presence and specific composition of rooted plants is a major factor influencing DNT rates of soils and sediments (Risgaard-Petersen and Jensen 1997). Plants can alter physicochemical factors known to control denitrification rates such as pH, oxygen, carbon sources and nitrate concentrations (Griffiths et al 1997;Gacia et al 2009).…”
mentioning
confidence: 99%
“…Moreover, macrophyte beds may enhance nutrient storage through increased sedimentation of fine particulate organic matter (Kleeberg, Köhler, Sukhodolova, & Sukhodolov, 2010;Sand-Jensen, 1998). Third, aquatic plants enhance NO 3 − -N removal via the accumulation of fine sediments in macrophytes beds that promote anoxic conditions and thus sediment denitrification (Petersen & Jensen, 1997).…”
Section: Introductionmentioning
confidence: 99%